Innovative preparation method of multi-layer composite heat-conducting material

By adopting the preparation method of multi-layer composite thermal conductivity materials, using materials such as copper powder, boron nitride particles and polyimide, combined with special surface treatment and bonding processes, the problems of limited thermal conductivity and insufficient bonding strength of existing thermal conductivity are solved, and efficient thermal conductivity and stability are achieved.

CN119704803AActive Publication Date: 2025-03-28SHENZHEN HFC SHIELDING PRODS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411905172.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-28
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

The thermal conductivity of existing thermal conductivity is limited and is easily corroded under special environments. The bonding strength between the layers is insufficient, resulting in separation and delamination under long-term use and external forces, affecting the thermal conductivity and overall stability.

Method used

The preparation method of multi-layer composite thermal conductivity is adopted. The copper powder is used as the bottom layer with high thermal conductivity, the intermediate layer formed by boron nitride particles, and the top layer composed of polyimide. Combined with special surface treatment and bonding processes, the thermal resistance of contact between each layer is reduced.

Benefits of technology

Excellent thermal conductivity is achieved, the bonding strength between the layers is enhanced, the overall stability and mechanical strength of the material are improved, stable thermal conductivity is maintained in high temperature environments, and the complexity and cost of the preparation process are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119704803A_ABST
    Figure CN119704803A_ABST
Patent Text Reader

Abstract

The invention discloses an innovative preparation method of a multi-layer composite heat-conducting material, and relates to the technical field of heat-conducting materials.The method comprises the specific steps that metal powder is selected as a metal heat-conducting gasket material, and the metal powder is copper powder.The multi-layer composite heat-conducting material has the excellent heat-conducting property and can be used as a metal heat-conducting gasket material; by compounding the metal heat-conducting layer, the inorganic nonmetal heat-conducting layer and the high-molecular polymer layer, the advantages of the materials of all the layers are fully played, copper powder in the metal heat-conducting layer has a high heat conductivity coefficient and can quickly transfer heat out, boron nitride in the inorganic nonmetal heat-conducting layer has good heat conductivity and high temperature resistance, and the heat-conducting performance of the metal heat-conducting layer is greatly improved. The high-temperature-resistant heat-conducting material can keep stable heat-conducting property in a high-temperature environment, the high-molecular polymer layer plays a role in protecting and enhancing the overall structural stability of the material, and due to the design of the multi-layer structure, heat can be efficiently transferred in the material, so that the heat-conducting efficiency of the material is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of thermal conductive materials, and in particular to an innovative preparation method of a multilayer composite thermal conductive material. Background Art

[0002] In today's era of rapid technological development, electronic equipment, new energy vehicles, aerospace and many other fields have made significant progress. With the continuous development of these fields, the performance requirements for materials are also increasing, especially in terms of thermal conductivity, which are inseparable from high-performance thermal conductive materials. Against this background, it is extremely important to develop a composite thermal conductive material with excellent thermal conductivity, good stability and processability.

[0003] However, the existing method for preparing thermally conductive materials uses a single thermally conductive material, which results in limited thermal conductivity and easy corrosion in some special environments. Secondly, the existing composite thermally conductive materials have problems in the bonding strength between the layers. When used for a long time and subjected to certain external forces, the layers are prone to separation and delamination, which seriously affects the thermal conductivity and overall stability of the material.

[0004] In summary, existing thermal conductive materials have certain limitations in terms of performance, structure, preparation process and cost, and it is difficult to meet the growing market demand. Therefore, developing a new type of multi-layer composite thermal conductive material to overcome the shortcomings of the existing technology, improve thermal conductivity, enhance the bonding strength between layers, simplify the preparation process and reduce costs has become an urgent problem to be solved in the current field of thermal conductive materials. Summary of the invention

[0005] The purpose of the present invention is to make up for the shortcomings of the prior art and provide an innovative preparation method for a multilayer composite thermal conductive material, which can achieve the optimal combination and distribution of materials with different thermal conductivity coefficients, using copper powder as a high thermal conductivity bottom layer, combined with a middle layer formed by boron nitride particles and a top layer composed of polyimide. This structural design not only fully utilizes the advantages of each material, but also greatly reduces the contact thermal resistance between layers through special surface treatment and bonding technology.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: an innovative preparation method of a multi-layer composite thermal conductive material, the specific steps of the method are:

[0007] S100, selecting metal powder as a material for the metal thermal conductive gasket, wherein the metal powder is copper powder with a particle size of 10 μm-50 μm, and performing surface treatment on the copper powder to remove surface oxides and impurities;

[0008] Boron nitride is selected as an inorganic non-metallic thermal conductive material, and the boron nitride is crushed and classified to obtain fine-particle boron nitride with a particle size of 1 μm-10 μm and coarse-particle boron nitride with a particle size of 10 μm-50 μm;

[0009] Selecting polyimide as the material of the high molecular polymer layer, the polyimide resin is thermoplastic polyimide;

[0010] S200, mixing the surface treated copper powder and a binder to form a copper powder slurry, wherein the binder is an inorganic adhesive, and the amount of the binder is 3% to 8% of the mass of the copper powder;

[0011] The copper powder slurry is pressed to prepare a metal heat-conducting layer;

[0012] S300, mixing boron nitride powders of different particle sizes uniformly according to a mass ratio to form a boron nitride mixed powder;

[0013] and mixing the boron nitride mixed powder with a binder and a solvent to form a boron nitride slurry;

[0014] The binder is an inorganic adhesive, the solvent is an organic solvent, the amount of the binder is 8%-15% of the mass of the boron nitride powder, and the amount of the solvent is 40%-60% of the mass of the boron nitride powder;

[0015] The boron nitride slurry is used to prepare an inorganic non-metallic heat-conducting layer by tape casting;

[0016] S400, uniformly mixing the polyimide resin and the auxiliary agent and drying them to form a polyimide mixture;

[0017] The polyimide mixture is extruded to prepare a high molecular polymer layer;

[0018] S500, placing a metal thermal conductive layer at the bottom layer, placing an inorganic non-metal thermal conductive layer on the metal thermal conductive layer, and placing a high molecular polymer layer on the inorganic non-metal thermal conductive layer, and using a hot pressing method to tightly combine the layers to form a multi-layer composite thermal conductive material.

[0019] Furthermore, the S100 surface treatment of the copper powder is specifically performed by chemical treatment and physical treatment methods to remove oxides and impurities on the surface of the copper powder. The chemical treatment adopts a pickling method, in which the copper powder is immersed in an acid solution, and the acid reacts with the oxide on the surface of the copper powder to generate water-soluble salts, and the impurities and reaction products are removed by water washing; the physical treatment adopts a mechanical grinding method, in which the oxides and impurities on the surface of the copper powder are removed by the action of mechanical force.

[0020] Furthermore, in the S200 pressing process, the copper powder slurry is placed in a mold and pressed under the conditions of a pressure of 8MPa-12MPa and a temperature of 140°C-160°C.

[0021] Furthermore, in the S300 tape casting process, the boron nitride slurry is poured into a tape casting machine and tape casting is performed at a tape casting speed of 0.5 m / min-2.5 m / min and a temperature of 50-80°C.

[0022] Furthermore, the mass ratio of the S300 fine-particle boron nitride with a particle size of 1 μm-10 μm to the coarse-particle boron nitride with a particle size of 10 μm-50 μm is 1:1.5-1:2.5.

[0023] Furthermore, in the S400 extrusion molding process, the polyimide mixture is placed in an extruder at a temperature of 200° C.-300° C. and a pressure of 2 MPa-5 MPa.

[0024] Furthermore, the S400 performs a pre-drying treatment on the polyimide mixture at a pre-drying temperature of 80° C.-120° C. for 2-4 hours to remove moisture and volatile substances in the polyimide mixture.

[0025] Furthermore, the S400 auxiliary agent is 0.5% by mass of an antioxidant, 1.5% by mass of silicone oil, 15% by mass of glass fiber and 1% by mass of a silane coupling agent.

[0026] Furthermore, the S500 hot pressing process is carried out at a temperature of 180° C.-220° C. and a pressure of 4 MPa-6 MPa.

[0027] Compared with the prior art, this innovative preparation method of a multilayer composite thermal conductive material has the following beneficial effects:

[0028] 1. The multilayer composite thermal conductive material of the present invention has excellent thermal conductivity. By compounding the metal thermal conductive layer, the inorganic non-metal thermal conductive layer and the high molecular polymer layer, the advantages of each layer of material are fully utilized. The copper powder in the metal thermal conductive layer has a high thermal conductivity coefficient and can quickly transfer heat; the boron nitride in the inorganic non-metal thermal conductive layer has good thermal conductivity and high temperature resistance, and can maintain stable thermal conductivity in a high temperature environment; the high molecular polymer layer plays a role in protecting and enhancing the overall structural stability of the material. The design of this multilayer structure enables heat to be efficiently transferred inside the material, greatly improving the thermal conductivity efficiency of the material.

[0029] 2. The present invention improves the mechanical strength and high temperature resistance of the inorganic non-metallic thermal conductive layer by precisely controlling the ratio of fine boron nitride particles to coarse particles, and selects thermoplastic polyimide as the outermost layer, which gives the entire composite system better flexibility and anti-aging ability, so that the obtained thermal conductive material is not only suitable for use in conventional environments, but also can cope with more demanding and harsh working conditions.

[0030] Other advantages, objectives and features of the present invention will be set forth in part in the following description and, in part, will be apparent to those skilled in the art based on an examination of the following or may be taught from the practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the prior art descriptions. Obviously, the drawings described below are only some embodiments of the present invention, and those skilled in the art can obtain other drawings based on these drawings without creative work.

[0032] Figure 1 The present invention is an operational flow chart of an innovative preparation method of a multi-layer composite thermal conductive material. DETAILED DESCRIPTION

[0033] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] Embodiment 1

[0035] This embodiment introduces in detail the use of a composite thermally conductive material prepared by an innovative method for preparing a multi-layer composite thermally conductive material in heat dissipation applications of electronic equipment to improve the stability and service life of the equipment, while ensuring the safe operation of the electronic equipment.

[0036] First, raw materials are prepared, including metal powder: high-purity copper powder with an average particle size of 20 microns is selected, and the copper powder is surface treated. First, the acid washing method is used to soak the copper powder in a dilute nitric acid solution for 25 minutes, and then washed with water, followed by mechanical grinding. The copper powder is ground using a ball mill at a speed of 450 revolutions per minute for 1.5 hours; inorganic non-metallic materials: boron nitride is selected as an inorganic non-metallic thermal conductive material, and the boron nitride is crushed and graded to obtain fine-particle boron nitride with an average particle size of 3 microns and coarse-particle boron nitride with an average particle size of 20 microns, and the mass ratio of fine particles to coarse particles is 1:1.6; polymer material: thermoplastic polyimide is used as the material of the polymer layer, a suitable polyimide resin is selected, and 0.4% by mass of an antioxidant, 1.2% of silicone oil, 13% of glass fiber and 0.8% of a silane coupling agent are added.

[0037] Then, the metal thermal conductive layer was prepared, and the pretreated copper powder was mixed with an appropriate amount of inorganic adhesive to form a copper powder slurry. The amount of the adhesive was 4% of the mass of the copper powder. The copper powder slurry was placed in a mold and pressed at a pressure of 9 MPa and a temperature of 145°C. The gaps between the copper powder particles were reduced, and the adhesive softened and filled between the copper powder particles to form a dense metal thermal conductive layer. As the pressure increased, the contact area between the copper powder particles increased, the thermal conductivity improved, the curing of the adhesive was promoted, and the strength and stability of the metal thermal conductive layer were improved. The pressing time was 1.2 hours, and a metal thermal conductive layer with a thickness of 0.45 mm was obtained.

[0038] Subsequently, an inorganic non-metallic thermal conductive layer is prepared. The boron nitride mixed powder is mixed with an appropriate amount of an inorganic adhesive and an organic solvent to form a boron nitride slurry. The amount of the binder is 10% of the mass of the boron nitride powder, and the amount of the solvent is 50% of the mass of the boron nitride powder. The boron nitride slurry is poured into a casting machine and evenly spread on the base belt of the casting machine. The casting is carried out at a casting speed of 1.2 m / min and a temperature of 60°C for 35 minutes. With the volatilization of the solvent and the solidification of the slurry, an inorganic non-metallic thermal conductive layer with a certain thickness of 0.28 mm is formed.

[0039] Next, a high molecular polymer layer was prepared by uniformly mixing the polyimide resin and the auxiliary agent, and then drying the mixture at 95°C for 2.5 hours to form a polyimide mixture. The polyimide mixture was placed in an extruder and extruded at 260°C and 3.5 MPa to obtain a high molecular polymer layer with a thickness of 0.18 mm.

[0040] Finally, composite molding is performed, with the metal thermal conductive layer placed at the bottom layer, the inorganic non-metallic thermal conductive layer placed on the metal thermal conductive layer, and the polymer layer placed on the inorganic non-metallic thermal conductive layer. Hot pressing is performed at a temperature of 195°C and a pressure of 4.5 MPa for 1.5 hours, so that each layer of material is tightly combined to form a multi-layer composite thermal conductive material.

[0041] Performance test: The thermal conductivity of the composite thermal conductive material is 75W / (m·K), the heat-resistant temperature reaches 340°C, and the deformation rate under pressure is 1.5%. The material can effectively reduce the temperature of the equipment by 15°C. The bending strength of the material is 140MPa, which has good mechanical strength and can withstand external forces without damage.

[0042] Embodiment 2

[0043] First, raw materials are prepared, including metal powder: high-purity copper powder with an average particle size of 25 microns is selected, and the copper powder is surface treated. The copper powder is soaked in a dilute sulfuric acid solution for 30 minutes using an acid pickling method, and then washed with water, and then ground with a grinder at a speed of 480 revolutions per minute for 1.8 hours; inorganic non-metallic materials: boron nitride is selected as an inorganic non-metallic thermal conductive material, and the boron nitride is crushed and graded to obtain fine-particle boron nitride with an average particle size of 4 microns and coarse-particle boron nitride with an average particle size of 25 microns, and the mass ratio of fine particles to coarse particles is 1:1.8; polymer material: thermoplastic polyimide is used as the material of the polymer layer, a suitable polyimide resin is selected, and 0.45% by mass of an antioxidant, 1.3% of silicone oil, 14% of glass fiber and 0.9% of a silane coupling agent are added.

[0044] Then, a metal thermal conductive layer was prepared, and the pretreated copper powder was evenly mixed with an appropriate amount of inorganic adhesive to form a copper powder slurry. The amount of the adhesive was 5% of the mass of the copper powder. The copper powder slurry was placed in a mold and pressed at a pressure of 10 MPa and a temperature of 150°C. During this process, the gap between the copper powder particles gradually decreased, and the adhesive softened and filled between the particles. As the pressure increased, the contact area of ​​the copper powder particles increased, the thermal conductivity was improved, and the adhesive was solidified, which enhanced the strength and stability of the metal thermal conductive layer. The pressing time was 1.3 hours, and a metal thermal conductive layer with a thickness of 0.48 mm was obtained.

[0045] Subsequently, an inorganic non-metallic thermal conductive layer was prepared. The boron nitride mixed powder was mixed with an appropriate amount of inorganic adhesive and organic solvent to form a boron nitride slurry. The amount of the binder was 11% of the mass of the boron nitride powder, and the amount of the solvent was 52% of the mass of the boron nitride powder. The boron nitride slurry was poured into a casting machine and cast at a casting speed of 1.4 m / min and a temperature of 65°C for 40 minutes. As the solvent evaporated and the slurry solidified, an inorganic non-metallic thermal conductive layer with a thickness of 0.3 mm was formed.

[0046] Next, a high molecular polymer layer was prepared by uniformly mixing the polyimide resin and the auxiliary agent, and then drying the mixture at 100°C for 2.8 hours to form a polyimide mixture. The polyimide mixture was placed in an extruder and extruded at 270°C and 4MPa to obtain a high molecular polymer layer with a thickness of 0.19mm.

[0047] Finally, composite molding is performed, with the metal thermal conductive layer placed at the bottom layer, the inorganic non-metallic thermal conductive layer placed on the metal thermal conductive layer, and the polymer layer placed on the inorganic non-metallic thermal conductive layer. Hot pressing is performed at a temperature of 200°C and a pressure of 5 MPa for 1.6 hours, so that each layer of material is tightly combined to form a multi-layer composite thermal conductive material.

[0048] Performance test: The thermal conductivity of the composite thermal conductive material is 80W / (m·K), the heat-resistant temperature reaches 350°C, and the deformation rate under pressure is 1.4%. The material can effectively reduce the temperature of the equipment by 16°C. The bending strength of the material is 145MPa, which has good mechanical strength and can withstand external forces without damage.

[0049] Embodiment 3

[0050] First, raw materials are prepared, including metal powder: high-purity copper powder with an average particle size of 30 microns is selected, and the copper powder is surface treated. The copper powder is first soaked in a hydrochloric acid solution for 35 minutes, then washed with water, and then ground with a ball mill at a speed of 500 revolutions per minute for 2 hours; inorganic non-metallic materials: boron nitride is selected as an inorganic non-metallic thermal conductive material, and the boron nitride is crushed and graded to obtain fine-particle boron nitride with an average particle size of 5 microns and coarse-particle boron nitride with an average particle size of 30 microns, and the mass ratio of fine particles to coarse particles is 1:2; polymer material: thermoplastic polyimide is used as the material of the polymer layer, a suitable polyimide resin is selected, and 0.5% by mass of an antioxidant, 1.4% of silicone oil, 15% of glass fiber and 1% of a silane coupling agent are added.

[0051] Then, the metal thermal conductive layer was prepared by mixing the pretreated copper powder with an appropriate amount of inorganic adhesive to form a copper powder slurry. The amount of the adhesive was 6% of the copper powder mass. The copper powder slurry was placed in a mold and pressed at a pressure of 11 MPa and a temperature of 155°C. The copper powder particles were tightly combined, and the adhesive played a full role, which improved the strength and stability of the thermal conductive layer. The pressing time was 1.4 hours, and a metal thermal conductive layer with a thickness of 0.5 mm was obtained.

[0052] Subsequently, an inorganic non-metallic thermal conductive layer was prepared. The boron nitride mixed powder was mixed with an appropriate amount of inorganic adhesive and organic solvent to form a boron nitride slurry. The amount of the binder was 12% of the mass of the boron nitride powder, and the amount of the solvent was 55% of the mass of the boron nitride powder. The boron nitride slurry was poured into a casting machine and cast at a casting speed of 1.6 m / min and a temperature of 70°C for 45 minutes to form an inorganic non-metallic thermal conductive layer with a thickness of 0.32 mm.

[0053] Next, a high molecular polymer layer was prepared by uniformly mixing the polyimide resin and the auxiliary agent, and then drying the mixture at 105°C for 3 hours to form a polyimide mixture. The polyimide mixture was placed in an extruder and extruded at 280°C and 4.5 MPa to obtain a high molecular polymer layer with a thickness of 0.2 mm.

[0054] Finally, composite molding is performed, with the metal thermal conductive layer placed at the bottom layer, the inorganic non-metallic thermal conductive layer placed on the metal thermal conductive layer, and the polymer layer placed on the inorganic non-metallic thermal conductive layer. Hot pressing is performed at a temperature of 205°C and a pressure of 5.5 MPa for 1.8 hours, so that each layer of material is tightly combined to form a multi-layer composite thermal conductive material.

[0055] Performance test: The thermal conductivity of the composite thermal conductive material is 85W / (m·K), the heat-resistant temperature reaches 360°C, and the deformation rate under pressure is 1.3%. The material can effectively reduce the temperature of the equipment by 17°C. The bending strength of the material is 150MPa, which has good mechanical strength and can withstand external forces without damage.

[0056] Embodiment 4

[0057] First, raw materials are prepared, including metal powder: high-purity copper powder with an average particle size of 35 microns is selected, and the copper powder is surface treated. The copper powder is soaked in a dilute sulfuric acid solution for 40 minutes using an acid pickling method, and then washed with water, and then ground with a grinder at a speed of 520 revolutions per minute for 2.2 hours; inorganic non-metallic materials: boron nitride is selected as an inorganic non-metallic thermal conductive material, and the boron nitride is crushed and graded to obtain fine-particle boron nitride with an average particle size of 6 microns and coarse-particle boron nitride with an average particle size of 35 microns, and the mass ratio of fine particles to coarse particles is 1:2.2; polymer material: thermoplastic polyimide is used as the material of the polymer layer, a suitable polyimide resin is selected, and 0.55% by mass of an antioxidant, 1.5% of silicone oil, 16% of glass fiber and 1.1% of a silane coupling agent are added.

[0058] Then, the metal thermal conductive layer was prepared by mixing the pretreated copper powder with an appropriate amount of inorganic adhesive to form a copper powder slurry. The amount of the adhesive was 7% of the mass of the copper powder. The copper powder slurry was placed in a mold and pressed at a pressure of 12 MPa and a temperature of 160°C to form a dense structure of the copper powder particles and improve the thermal conductivity. The pressing time was 1.5 hours, and a metal thermal conductive layer with a thickness of 0.55 mm was obtained.

[0059] Subsequently, an inorganic non-metallic thermal conductive layer was prepared. The boron nitride mixed powder was mixed with an appropriate amount of an inorganic adhesive and an organic solvent to form a boron nitride slurry. The amount of the binder was 13% of the mass of the boron nitride powder, and the amount of the solvent was 58% of the mass of the boron nitride powder. The boron nitride slurry was poured into a casting machine and cast at a casting speed of 1.8 m / min and a temperature of 75°C for 50 minutes to form an inorganic non-metallic thermal conductive layer with a thickness of 0.35 mm.

[0060] Next, a high molecular polymer layer was prepared by uniformly mixing the polyimide resin and the auxiliary agent, and then drying the mixture at 110°C for 3.2 hours to form a polyimide mixture. The polyimide mixture was placed in an extruder and extruded at 290°C and 5MPa to obtain a high molecular polymer layer with a thickness of 0.22mm.

[0061] Finally, composite molding is performed, with the metal thermal conductive layer placed at the bottom layer, the inorganic non-metallic thermal conductive layer placed on the metal thermal conductive layer, and the polymer layer placed on the inorganic non-metallic thermal conductive layer. Hot pressing is performed at a temperature of 210°C and a pressure of 6MPa for 2 hours to tightly combine the layers of material to form a multi-layer composite thermal conductive material.

[0062] Performance test: The thermal conductivity of the composite thermal conductive material is 90W / (m·K), the heat-resistant temperature reaches 370°C, and the deformation rate under pressure is 1.2%. The material can effectively reduce the temperature of the equipment by 18°C. The bending strength of the material is 155MPa, which has good mechanical strength and can withstand external forces without damage.

[0063] Embodiment 5

[0064] First, raw materials are prepared, including metal powder: high-purity copper powder with an average particle size of 40 microns is selected, and the copper powder is surface treated. The copper powder is first soaked in a hydrochloric acid solution for 45 minutes, then washed with water, and then ground with a ball mill at a speed of 550 revolutions per minute for 2.5 hours; inorganic non-metallic materials: boron nitride is selected as an inorganic non-metallic thermal conductive material, and the boron nitride is crushed and graded to obtain fine-particle boron nitride with an average particle size of 7 microns and coarse-particle boron nitride with an average particle size of 40 microns, and the mass ratio of fine particles to coarse particles is 1:2.5; polymer material: thermoplastic polyimide is used as the material of the polymer layer, a suitable polyimide resin is selected, and 0.6% by mass of an antioxidant, 1.6% by mass of silicone oil, 17% by mass of glass fiber and 1.2% by mass of a silane coupling agent are added.

[0065] Then, the metal thermal conductive layer was prepared by mixing the pretreated copper powder with an appropriate amount of inorganic adhesive to form a copper powder slurry. The amount of the adhesive was 8% of the mass of the copper powder. The copper powder slurry was placed in a mold and pressed at a pressure of 13 MPa and a temperature of 165°C. The copper powder particles were tightly combined to form a high-strength thermal conductive layer. The pressing time was 1.6 hours, and a metal thermal conductive layer with a thickness of 0.6 mm was obtained.

[0066] Subsequently, an inorganic non-metallic thermal conductive layer was prepared. The boron nitride mixed powder was mixed with an appropriate amount of inorganic adhesive and organic solvent to form a boron nitride slurry. The amount of the binder was 14% of the mass of the boron nitride powder, and the amount of the solvent was 60% of the mass of the boron nitride powder. The boron nitride slurry was poured into a casting machine and cast at a casting speed of 2 m / min and a temperature of 80°C for 55 minutes to form an inorganic non-metallic thermal conductive layer with a thickness of 0.38 mm.

[0067] Next, a high molecular polymer layer was prepared by uniformly mixing the polyimide resin and the auxiliary agent, and then drying the mixture at 115° C. for 3.5 hours to form a polyimide mixture. The polyimide mixture was placed in an extruder and extruded at 300° C. and 5.5 MPa to obtain a high molecular polymer layer with a thickness of 0.25 mm.

[0068] Finally, composite molding is performed, with the metal thermal conductive layer placed at the bottom layer, the inorganic non-metallic thermal conductive layer placed on the metal thermal conductive layer, and the polymer layer placed on the inorganic non-metallic thermal conductive layer. Hot pressing is performed at a temperature of 215°C and a pressure of 6.5 MPa for 2.2 hours, so that each layer of material is tightly combined to form a multi-layer composite thermal conductive material.

[0069] Performance test: The thermal conductivity of the composite thermal conductive material is 95W / (m·K), the heat-resistant temperature reaches 380°C, and the deformation rate under pressure is 1.1%. The material can effectively reduce the temperature of the equipment by 19°C. The bending strength of the material is 160MPa, which has good mechanical strength and can withstand external forces without damage.

[0070] Comparative Example

[0071] A single metal copper sheet is used as the heat conducting material without multi-layer composite treatment.

[0072] Performance test: The thermal conductivity of the single metal copper sheet thermal conductive material is 60W / (m·K), the heat resistance temperature reaches 300°C, and the deformation rate under pressure is 2.5%. The material can effectively reduce the temperature of the equipment by 10°C. The bending strength of the material is 120MPa, and the mechanical strength is relatively weak, and it is easy to be damaged when subjected to external force.

[0073] In summary, by performing performance tests on the embodiments and comparative examples of the multilayer composite thermally conductive material, from the perspective of thermal conductivity, the embodiments 1 to 5 gradually improve with the change of parameters, indicating that the multilayer composite structure has significantly improved thermal conductivity; in terms of heat resistance temperature, the embodiments are also significantly higher than the comparative examples, indicating that the material can work stably in a high temperature environment; in terms of deformation rate, the embodiments are controlled at a relatively low level, reflecting good structural stability; in terms of reducing equipment temperature and bending strength, the embodiments can effectively reduce equipment temperature and have a relatively high bending strength, and can withstand external forces; the comparative examples are at a disadvantage in all performances, and the multilayer composite thermally conductive material of the present invention has excellent performance. The performance test results of embodiments 1-5 and the comparative examples are shown in the following table:

[0074]

[0075] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

Claims

1. An innovative method for preparing a multilayer composite thermally conductive material, characterized in that: The specific steps of this method are: S100, selecting metal powder as a material for the metal thermal conductive gasket, wherein the metal powder is copper powder with a particle size of 10 μm-50 μm, and performing surface treatment on the copper powder to remove surface oxides and impurities; Boron nitride is selected as an inorganic non-metallic thermal conductive material, and the boron nitride is crushed and classified to obtain fine-particle boron nitride with a particle size of 1 μm-10 μm and coarse-particle boron nitride with a particle size of 10 μm-50 μm; Selecting polyimide as the material of the high molecular polymer layer, the polyimide resin is thermoplastic polyimide; S200, mixing the surface treated copper powder and a binder to form a copper powder slurry, wherein the binder is an inorganic adhesive, and the amount of the binder is 3% to 8% of the mass of the copper powder; The copper powder slurry is pressed to prepare a metal heat-conducting layer; S300, mixing boron nitride powders of different particle sizes uniformly according to a mass ratio to form a boron nitride mixed powder; and mixing the boron nitride mixed powder with a binder and a solvent to form a boron nitride slurry; The binder is an inorganic adhesive, the solvent is an organic solvent, the amount of the binder is 8%-15% of the mass of the boron nitride powder, and the amount of the solvent is 40%-60% of the mass of the boron nitride powder; The boron nitride slurry is used to prepare an inorganic non-metallic heat-conducting layer by tape casting; S400, uniformly mixing the polyimide resin and the auxiliary agent and drying them to form a polyimide mixture; The polyimide mixture is extruded to prepare a high molecular polymer layer; S500, placing a metal thermal conductive layer at the bottom layer, placing an inorganic non-metal thermal conductive layer on the metal thermal conductive layer, and placing a high molecular polymer layer on the inorganic non-metal thermal conductive layer, and using a hot pressing method to tightly combine the layers to form a multi-layer composite thermal conductive material.

2. According to claim 1, a method for preparing a multilayer composite thermally conductive material is characterized in that: The S100 surface treatment of the copper powder specifically adopts chemical treatment and physical treatment methods to remove oxides and impurities on the surface of the copper powder. The chemical treatment adopts a pickling method, in which the copper powder is immersed in an acid solution, and the acid reacts with the oxides on the surface of the copper powder to generate water-soluble salts, and the impurities and reaction products are removed by water washing; the physical treatment adopts a mechanical grinding method, in which the oxides and impurities on the surface of the copper powder are removed by the action of mechanical force.

3. According to claim 1, a method for preparing a multilayer composite thermally conductive material is characterized in that: The S200 pressing process is to put the copper powder slurry into a mold and press it under the conditions of a pressure of 8MPa-12MPa and a temperature of 140°C-160°C.

4. According to claim 1, a method for preparing a multilayer composite thermally conductive material is characterized in that: The S300 tape casting process is to pour the boron nitride slurry into a tape casting machine and perform tape casting at a casting speed of 0.5 m / min-2.5 m / min and a temperature of 50-80°C.

5. According to claim 1, a method for preparing a multi-layer composite thermally conductive material is characterized in that: The mass ratio of the S300 fine-particle boron nitride with a particle size of 1 μm-10 μm to the coarse-particle boron nitride with a particle size of 10 μm-50 μm is 1:1.5-1:2.

5.

6. According to claim 1, a method for preparing a multi-layer composite thermally conductive material is characterized in that: The S400 extrusion molding process is to put the polyimide mixture into an extruder at a temperature of 200° C.-300° C. and a pressure of 2 MPa-5 MPa.

7. The innovative method for preparing a multilayer composite thermally conductive material according to claim 1, characterized in that: The S400 performs pre-drying treatment on the polyimide mixture at a pre-drying temperature of 80° C.-120° C. for 2-4 hours to remove moisture and volatile substances in the polyimide mixture.

8. The innovative method for preparing a multilayer composite thermally conductive material according to claim 1, characterized in that: The S400 auxiliary agent comprises 0.5% by mass of an antioxidant, 1.5% by mass of silicone oil, 15% by mass of glass fiber and 1% by mass of a silane coupling agent.

9. The innovative method for preparing a multi-layer composite thermally conductive material according to claim 1, characterized in that: The S500 hot pressing process is carried out at a temperature of 180° C.-220° C. and a pressure of 4 MPa-6 MPa.

Citation Information

Patent Citations

  • Heat conductive insulation sheet and structural adhesive

    CN102602076A

  • High thermal conductive metal substrate

    CN103042762A

  • High-thermal-conductivity polyimide multilayer composite film and preparation method thereof

    CN110626030A

  • Heat-conducting composite film, insulating metal plate as well as preparation method and application of insulating metal plate

    CN114316564A

  • Heat-conducting polyimide film added with inorganic additive as well as preparation method and application of heat-conducting polyimide film

    CN117430848A